Resistência à insulina em pré-adolescentes obesos : um fator de risco para síndrome metabólica na vida adulta - Souza, Dayane Aparecida de (2023)
The accelerated growth of metabolic diseases such as obesity, type 2 diabetes mellitus and hypertension has proved to be one of the main health problems in the world. Clinical and experimental evidence shows that the late onset of these comorbidities are often associated with exposure to physiological stressors such as maternal metabolic disorders or nutritional insults that occurred in intrauterine/neonatal life. We aimed to evaluate the relationship between overweight in pre-adolescents of both sexes, risk factors for metabolic syndrome and perinatal exposure to nutritional insults. This is a cross-sectional study, with descriptive objectives and quantitative analysis, carried out with pre-adolescents belonging to the age groups of 10 to 14 years old enrolled in agreed public schools in the city of Sinop, MT, Brazil. All protocols performed were approved by the ethics committee for research with human beings. After applying the inclusion and exclusion criteria, 81 adolescents remained who were divided into 4 groups according to body mass index (BMI) and gender, namely: Eutrophic male and female and Overweight male and female. Data were analyzed using the Graphpad Prism® program, where those that assumed normal distribution were submitted to one-way analysis of variance (one-way ANOVA) with post Tukey test, while the others were submitted to the Kruskal-Wallis test and post Dunn test. Results are presented as mean±SD, median, 1st and 3rd quartiles. There was no statistical difference between the groups in terms of birthweight (P>0.05), and no correlation was observed between this parameter and the metabolic alterations observed in preadolescents. While there was no association between low birthweight and overweight in preadolescents, it was seen that the prevalence of overweight/obesity among pre-adolescents whose mothers reported obesity during pregnancy was 2-fold higher. Both girls and boys in the overweight group showed an increase in waist-hip circumference (P<0.01), with girls showing a stronger correlation between waist circumference and BMI (r=0.903) than boys (r=0.850). Although no difference was observed in the lipid profile and fasting blood glucose between overweight pre-adolescents (P>0.05), an increase in fasting insulinemia (~214%, P<0.01), HOMA-IR (~170%, P<0.05), HOMA-β (~190%, P<0.01) and SBP (~11%, P<0.05) was observed in overweight girls compared to eutrophic. In summary, among overweight preadolescents in the analyzed population, we concluded that girls are more prone to the development of metabolic disorders such as central obesity, hyperinsulinemia, insulin resistance, lower functional capacity of pancreatic β-cells and increased SBP, which may be associated with the presence of maternal obesity during pregnancy.